A palavra como "aparelho motor": um estudo da linguagem em matéria e memória - Temporal, Vanessa de Oliveira (Universidade Federal de São Carlos, 2014)
After a short resumption of Bergson s thesis about the inadequacy of language s expression of reality, which permeates all his works, this dissertation intends to discuss how Matter and Memory contemplates a deeper reflection on this subject as it presents the notion of motor mechanism , allowing to foresee the bodily grounds of practical habits and pointing out the problem of their transposition to speculative thought without criticism. In general, we intend to comprehend how Bergson s language conception based on a definition of word as an entity of motor order or more specifically as motor mechanism announces an extralinguistic access to reality when it directs the philosophical study to the notion of image and to the five figures which permeates the last chapters of Matter and Memory.
Keywords: Filosofia - história; Bergson, Henri Louis, 1859-1941; Linguagem; Intuição; Aparelho-motor; Language; Motor mechanisms; Intuition; CIENCIAS HUMANAS::FILOSOFIA